Geomechanical behaviors of bimrocks - Yu, Wang, 1982- (Boca Raton : CRC Press, 2021)
"This book is intended as a reference book for advanced graduate students and research engineers in block-in-matrix rocks (bimrocks) or soil and rock mixtures (SRMs) or rock and soil aggregate (RSA). Bimrocks are complex formations characterized by competent rock inclusions floating in a weaker matrix. Typical types of bimrocks include a series of mixed geological or engineering masses such as mélanges, fault rocks, coarse pyroclastic rocks, breccias, sheared serpentines and waste dump mixture. Bimrock is especially different from the general soil and rock material, and the detection of the damage and fracture is still wide open to innovative research. Globally, there is widespread interest in investigating the geomechanical behaviors of bimrocks, such as deformation and strength characteristics, damage and fracture evolution and stability prediction of bimrock construction. However, the meso-structure factors control the whole mechanical properties of bimrocks, the source of the macroscopic deformation phenomenon is the meso-structural changes. Therefore, evaluation of the mesoscopic physical and mechanical properties, together with advanced testing technique, are attractive research topics in rock mechanics. As a result, comprehensive macroscopic and mesoscopic experimental investigations should be conducted to reveal the damage and fracturing mechanical behaviors of bimrock. The readers of this work can gain new insights into the meso-structural changes of bimrocks subjected to different stress paths. The book is expected to improve the understanding of the mesoscopic damage and fracturing mechanisms of bimrocks and can be helpful to predict the stability of rock structures where rock mass is subjected to complex loading conditions"--
Macro-meso geomechanical behaviors of bimrocks -- Ultrasonic and mechanical characteristics of bimrocks -- Static fracture evolutioon of bimrocks revealed by in-situ CT technique -- Dynamic behavior characterization using CT technique -- Flow and stress coupled characteristics of bimrock -- Investigation on piping disaster in bimsoils.
OCLC-licensed vendor bibliographic record.
Keywords: Block theory (Rock mechanics); Schists; Soil mechanics; Conglomerate; TECHNOLOGY / Mining